Capital Raising Plan to be A National Bank in 2015, Case of Bank BJB - Junita, Milda; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2014)
Abstract.Â Bank BJB as a regional bank will be directed to upgrade to the 'next level' in order to become a national bank which will be growing continuously with high profitability level ("A Strong Sustainable and Profitable Bank") to get higher assets and earnings, stronger in capital and better in service in 2015. According to the data 31 December 2013, based on the Indonesian Banking Architecture (API), Bank BJB is still categorized as a bank that has regional focus with total capital (Tier I and Tier II) Rp 5.7 trillions and based on multiple license regulation, Bank BJB categorized as bank in Caterory III with Tier I capital Rp 5.6 trillions.To become bank that categorized as National Bank in Category III which has capital (Tier I and Tier II) at least Rp 10 Trillion as stated in Indonesian Banking Architecture (API). Bank BJB needs additional Tier I Capital amount Rp 4.3 trillion so that Bank BJB can get capital Rp 10 trillion by 2015 and meet its target to become National Bank in Category III in 2015. If Bank BJB do not reviset its strategies so that Bank BJB cannot meet its target in 2015. There are four strategies alternative to raise capital. In organic growth strategy Bank BJB can reach capital Rp 10 Trillion in 2018. In reducing dividend payout ratio become 53% Bank BJB can reach capital Rp 10 Trillion in 2017. In right issue proceeds Rp 2.5 Trillion Bank BJB can reach capital Rp 10 Trillion in 2015. In issue bonds Rp 5 Trillion gradually in 2015 and 2015 Bank BJB can reach capital Rp 10 Trillion in 2017. So that right issue is choosen with proceeds Rp 2.5 Trillion.Keywords: Bank Business Plan, Tier I, Tier II, capital raising, source of fund.Â